Videogame che legge nel pensiero - Puto, Małgorzata (Romanica Silesiana)
Alessandro Militi, by means of his protagonist, who plays the videogame called Fuffa, presents his vision of the society overwhelmed by technological progress, and in consequences deprived of real moral values. The author presents the existing sociocultural phenomena in a very realistic-mimetic and reliable way, expressing his reluctance towards the objects suppressing human sensitivity and the need to communicate with other people not only by means of internet and mobile phone. Economic development, improving of the conditions of living, bigger selection of goods entail negative aspects. A man distances himself from spiritual values and becomes a handicapped and indifferent creature. The coexistance of the elements of virtual and real is plain and clear; a man being between these opposing poles cannot fully free himself from the artificial. The only way out from this situation appears when the game is over. Key words: Videogame, virtual, real, mimesis.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />